Benefits of Biogas as a Renewable Energy Source in Supporting Sustainable Development Goals (SDGs) in the KPSP Setia Kawan Region, Pasuruan, Indonesia - Yudi Ariyanto; Teguh Soedarto (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2025)
KPSP (Cooperative of Dairy Farmers) Setia Kawan, Nongkojajar, Pasuruan, East Java, Indonesia, is one of the largest cooperatives of dairy farms in Indonesia, which consists of approximately 11,225 farmers with a population of 25,273 dairy cows. Milk production to date has reached ± 94,000 liters per day or ± 1,128,000 liters per year, which is increasing due to the milk needs of the Indonesian people, with the number of dairy cattle population in the KPSP Setia Kawan area has the potential to produce renewable energy sources, namely biogas by processing livestock manure waste. Processing livestock waste into biogas is very profitable and can play a role in the Sustainable Development Goals (SDGs) program.Processing livestock waste into renewable Energy through biogas is very appropriate because biogas can balance the use of fossil energy, which is increasingly depleting, and the use of biogas is more environmentally friendly and has economic and social benefits as a pillar of sustainable developmentThis systematic review comprehensively examines the benefits of biogas as renewable Energy in supporting the sustainable development goals program based on the three pillars of sustainable development, namely environment, economy, and social, that support the SDGs Sustainable Development Goals program. The research shows a powerful contribution benefit between the three pillars of sustainable development and sustainable development goals at KPSP Setia Kawan on biogas as renewable Energy.